2019
DOI: 10.1186/s12889-019-7372-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status using anthropometric variables by multivariate analysis

Abstract: Background Undernutrition is a serious health problem and highly prevalent in developing countries. There is no as such confirmatory test to measure undernutrition. The objective of the present study is to determine a new Composite Score using anthropometric measurements. Composite Score was then compared with other methods like body mass index (BMI) and mid-upper arm circumference (MUAC) classification, to test the significance of the method. Methods Anthropometric dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 33 publications
2
48
1
2
Order By: Relevance
“…Anthropometric measurement was done. 15 In the present study, according to WHO BMI classification, 16 between 18.5 to 24.9 and 17% had BMI less than 18.5. 17 In contrast to our study, a hospitalbased study was carried out by Hajira et al in Rehman Medical Institute, Peshawar, Pakistan which showed that 54% of the hemodialysis patients had low BMI indicating malnutrition.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Anthropometric measurement was done. 15 In the present study, according to WHO BMI classification, 16 between 18.5 to 24.9 and 17% had BMI less than 18.5. 17 In contrast to our study, a hospitalbased study was carried out by Hajira et al in Rehman Medical Institute, Peshawar, Pakistan which showed that 54% of the hemodialysis patients had low BMI indicating malnutrition.…”
Section: Discussionsupporting
confidence: 43%
“…19 Recent study (2019) done by Bhattacharya and her colleagues in West Bengal, India also strongly support our study in which she had shown that 42.9% of male and 70.2% of female had malnutrition on the basis of MUAC. 15 In the present study 56.6% of the patients had low serum albumin i.e., below 3.5gm/ dl and 43.4% of the patients had normal serum albumin level (3.5-5.5 gm/dl). Similar observation was documented previously in some parts of China by Zhang et al in which they had reported 53.72% of CKD patients with albumin level below 3.5 gm/dl.…”
Section: Discussionsupporting
confidence: 40%
“…90 Body mass index (BMI) and waist/hip ratio will be calculated. 91 Percentage of lean and fat mass will be obtained using the BOD POD (Cosmed, Rome, Italy), an Air Displacement Plethysmograph using whole body densitometry, to determine body composition (fat vs lean % fat mass), 92 and conducted following manufacturer protocols for measurement. This will require subjects to fast for 8 hours prior to testing and wear tightly fitted gym clothes for measurement.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Nutritional status of a woman is important for positive pregnancy outcome (1,2) . The nutritional status can be assessed using different parameters, one of them being the Mid-upper arm circumference (MUAC) (2)(3)(4) , a simple measurement used to evaluate the nutritional status of an individual (5,6) and serves as a surrogate of the body mass in pregnant women (7). The MUAC is one of the most effective ways of determining short term change in the nutritional status of an identi ed population (8).…”
Section: Introductionmentioning
confidence: 99%